Employment status and educational attainment among disabled Ghanaians - Clifford Afoakwah; Fatima Dauda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
People with disabilities in Ghana and other developing economies are discriminated against in many fundamental elements of human empowerment such as education and employment. While some employers are unwilling to hire, the educational systems do not provide enabling environment for a good education. This paper explores employment and educational attainment among people with disabilities. Although, people with disabilities have low employment probabilities, our finding suggests that education increases their chance of employment. Moreover, while women with disabilities are dually disadvantaged in the labour market, educational facilities far from home lead to improvement in disabled children's educational achievements.
Keywords: I31; I21; J71; 330; people with disabilities; paid employment; basic education; Ghana